2003
DOI: 10.1679/aohc.66.289
|View full text |Cite
|
Sign up to set email alerts
|

Synovial membrane in the temporomandibular joint-Its morphology, function and development

Abstract: This paper reviews recent findings of the synovial membrane, in particular the morphology, function and development of synovial lining cells, in the temporomandibular joint (TMJ). Electron microscopic studies have confirmed the synovial membrane in TMJ consists of macrophage-like type A cells and fibroblast-like type B cells identical to those in other systematic joints. The macrophage-like type A cells react with anti-macrophage and macrophage-derived substances including the major histocompatibility class II… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
76
0
11

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 72 publications
(88 citation statements)
references
References 66 publications
1
76
0
11
Order By: Relevance
“…Its synovial lining layer contains two types of synovial lining cells: macrophage-like type A and fibroblast-like type B cells (for review, see Nozawa-Inoue et al, 2003), as reported in other systemic joints (for review, see Iwanaga et al, 2000). The type A cell is characterized by numerous vacuoles, lysosomes, nuclei with rich heterochromatin, and cell surface filopodia, while the type B cell possesses a well-developed rough endoplasmic reticulum (rER), a nucleus with less chromatin, and cytoplasmic long projections.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Its synovial lining layer contains two types of synovial lining cells: macrophage-like type A and fibroblast-like type B cells (for review, see Nozawa-Inoue et al, 2003), as reported in other systemic joints (for review, see Iwanaga et al, 2000). The type A cell is characterized by numerous vacuoles, lysosomes, nuclei with rich heterochromatin, and cell surface filopodia, while the type B cell possesses a well-developed rough endoplasmic reticulum (rER), a nucleus with less chromatin, and cytoplasmic long projections.…”
mentioning
confidence: 99%
“…The type A cell is characterized by numerous vacuoles, lysosomes, nuclei with rich heterochromatin, and cell surface filopodia, while the type B cell possesses a well-developed rough endoplasmic reticulum (rER), a nucleus with less chromatin, and cytoplasmic long projections. In addition, some ultrastructural investigations have pointed out that the fibroblast-like type B cells had invaginations reminiscent of caveolae in their cell membrane (Graabaek, 1984;Iwanaga et al, 2000;Nozawa-Inoue et al, 2003). However, both the nature and the functional significance of this structure remain unclear.…”
mentioning
confidence: 99%
“…A series of ultrastructural surveys has agreed that the synovial lining cell layer consists of two kinds of synoviocytes-including macrophage-like type A and fibroblastlike type B cells-which respectively function in the resorption and synthesis/secretion of synovial fluids (for reviews, Iwanaga et al, 2000;Nozawa-Inoue et al, 2003). However, immunoelectron microscopy pointed out the possibility that type B synoviocytes in the TMJ could be further divided into some phenotypes by their immunocytochemical properties (Nozawa-Inoue et al, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…The synovial membrane in the TMJ consists of a surface synovial lining layer and a connective sublining layer. In addition, the synovial lining layer contains two types of synovial lining cells: macrophage-like type A and fibroblast-like type B cells (for review, see Nozawa-Inoue et al, 2003). The fibroblast-like type B cells have important functions in the production/secretion of type I and II collagens, fibronectin, and glycosaminoglycans-including hyaluronic acid-into the synovial interstitium and fluids.…”
mentioning
confidence: 99%
See 1 more Smart Citation